We Are Not Alone: A Classroom Full Of Teachers - Millen-Penn, Ken (Teaching History: A Journal of Methods, 1997)
Renowned mountain climber Willi Unsoeld once told a group of climbers to "take care of each other. Share your energies with the group. No one must feel alone, cut off, for that is when you do not make it."1 Cooperation is a vital component of human life, a vital component of success. However, until recently America's schools and colleges have functioned under the idea that cooperation in education was somehow wrong and counterproductive. Most schools and colleges continue to emphasize the traditional teaching method of lecture-a one-way monologue where the professor gives facts and knowledge and where students passively listen, take notes, and absorb knowledge. Sharan and Sharan have noted that traditional education makes students consumers and teachers feeders-whereby one individual, the instructor, decides what is on the menu, the size of the portions, and how fast the consumer, that is the student, must ingest.2 And, to continue with this analogy, the consuming student is asked to regurgitate what has been consumed.